PERAN AUDITOR INTERNAL DAN PENGENDALIAN INTERN DALAM PELAKSANAAN TATA KELOLA PEMERINTAHAN YANG BAIK - Widia Astuty (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2016)
This study aimed at obtain the interpretation of: (1) The effect of the role of the internal auditor on the good governance implementation; (2) Effect of internal control on the good governance implementation; and (3) Effect of the role of internal auditors and internal control simultaneously on the good governance implementation.            This research method using descriptive and verificative types. The unit of analysis in this study are all the Provincial Office of North Sumatra. Descriptive analyzes were performed to obtain a picture of the role of internal auditors and internal control and the implementation of good governance. While verificative analyzes to examine the effect of the role of internal auditors and internal control partially and simultaneously on the good governance implementation with Path analysis.            The results showed that: (1) There is the influence of the role of the internal auditor on the good governance implementation; (2) There is an effect of the internal control on the good governance implementation            ; and (3) There is the influence of the role of internal auditors and internal control simultaneously on the good governance implementation. Keywords: Internl Auditor, Internal Control, Good Governance